Performance of differential time to positivity as a routine diagnostic test for catheter-related bloodstream infections: a single-centre experience. (March 2020) - Orihuela-Martín, J.; Rodríguez-Núñez, O.; Morata, L.; Cardozo, C.; Puerta-Alcalde, P.; Hernández-Meneses, M.; Ambrosioni, J.; Linares, L.; Bodro, M.; de los Angeles Guerrero-León, M.; del Río, A.; Garcia-Vidal, C.; et al.
ABSTRACT: Objective: To assess the performance of differential time to positivity (DTP) for the diagnosis of catheter-related bloodstream infections (CRBSI). Methods: From all episodes of bloodstream infections (BSI) diagnosed during a 15-year period (2003–17) those in which a paired set of blood cultures drawn from a catheter and a peripheral vein were positive for the same microorganism and had a clinically and/or microbiologically defined source were selected. To assess diagnostic discrimination ability and accuracy of DTP for CRBSI, area under the receiver operating characteristic curves (AUC) and performance characteristics of a DTP ≥2 h were computed. Results: A total of 512 BSI were included, of which 302 (59%) were CRBSI. Discrimination ability of DTP was low for Staphylococcus aureus (AUC 0.656 ± 0.06), coagulase-negative staphylococci (AUC 0.618 ± 0.081), enterococci (AUC 0.554 ± 0.117) and non-AmpC-producing Enterobacteriaceae (AUC 0.653 ± 0.053); moderate for Pseudomonas aeruginosa (AUC 0.841 ± 0.073), and high for AmpC-producing Enterobacteriaceae (AUC 0.944 ± 0.039). For the entire sample, DTP had a low-to-moderate discrimination ability (AUC 0.698 ± 0.024) . A DTP ≥2 h has a low sensitivity for coagulase-negative staphylococci (60%) and very low for S. aureus (34%), enterococci (40%) and non-AmpC-producing Enterobacteriaceae (42%). A DTP cut-off of 1 h improved sensitivity (90%) for AmpC-producing Enterobacteriaceae . Conclusions: Differential time to positivity performs well for diagnosing CRBSI only when AmpC-producing Enterobacteriaceae and P. aeruginosa are involved. Performance is low for common Gram-positive organisms and non-AmpC-producing enteric bacilli; a negative test should not be used to rule out CRBSI due to these microorganisms. A DTP ≥1 h may improve accuracy for AmpC-producing Enterobacteriaceae, particularly Enterobacter spp.